Premedication with simethicone for improving the quality of gastric mucosal visualization: a double-blind randomized controlled trial - Duez, Leo; Gkolfakis, Paraskevas; Bastide, Marine; Vuckovic, Clemence; Musala, Carmen; Van Gossum, Marc; Hoyois, Alice; Mulkay, Jean-Pierre; Eisendrath, Pierre (Endoscopy International Open, 2022)
Background and study aims Saliva, bubbles, or mucus can limit gastric mucosal visualization (GMV), increasing the risk of missed lesions such as gastric cancer. Several studies using endoscopy photodocumentation-based scores have reported increased quality of GMV when mucolytic and/or defoaming agents are administered. This single-center, prospective, double-blind, randomized, placebo-controlled trial aimed to evaluate whether simethicone administration could improve GMV.Patients and methods Patients were randomly assigned (1:1) to receive either 200 mg of simethicone (Group A) or placebo (Group B). Two independent endoscopists reviewed the entire video recording from each examination to assess the quality of GMV. The primary outcome was the rate of adequate GMV, defined as the percentage of patients in each group with a video score scale < 7 based on gastric visualization of five gastric landmarks. Secondary outcomes included procedure duration, patient satisfaction, and side effects.Results A total of 110 consecutive outpatients were randomly assigned to one of the two study groups (11 were excluded for various reasons). For the primary endpoint, 32 patients (61.5 %) in group A achieved adequate GMV compared to one of 47 (2.1 %) in group B (odds ratio [95 % confidence interval]: 73.6 [9.4–576.6]; P < 0.001). Median procedure time did not differ between the groups (P = 0.55), and no differences were detected in patient satisfaction (P = 0.18) or side effects (P = 0.58). No serious adverse events were documented.Conclusions Premedication with simethicone before upper gastrointestinal endoscopy significantly improves the quality of GMV without affecting the duration of the examination, patient satisfaction, and the rate of side effects.